Impact of closure of educational institutions due to COVID-19 lockdown on overall subjective wellbeing of adolescents and youth: Cross-sectional survey, India - Rawal, Tina; Mishra, Vijay Kumar; Sharda, Shefali Godura; Sharma, Kiran; Mehta, Rajesh; Kulkarni, Muralidhar M.; Goel, Sonu; Arora, Monika (Frontiers in Psychology, 2022)
Background Students were confined to their homes due to the national closure of educational institutions during the COVID 19 pandemic, thus presenting an unprecedented risk to children’s education, protection, and wellbeing. Aim This study aimed to understand the determinants of subjective wellbeing of adolescents and youth (aged 11–21 years) during the COVID-19 pandemic in India. Materials and methods A cross-sectional web-based survey was adapted, pre-tested, and finalized to obtain the participant’s responses from schools and colleges. Participants aged 11–17 years were engaged through schools. Consent procedures were followed. The survey link was disseminated through social media for the participants aged 18–21 years. The survey was made available in English and Hindi. The data was collected from March-June, 2021. Results Overall, 1,596 students completed the survey. Out of 1,596 students, 1252 (78%) were below 18 years and 344 (21.5%) participants were 18 years and above. Results suggest a statistically significant (p < 0.01) difference in the level of student’s life satisfaction before and during the COVID-19 pandemic. Of the students who were dissatisfied with their general life during the pandemic, nearly 63.4% felt sadness followed by other feelings, i.e., boredom (around 60.5%), loneliness (63.7%), and anxiety (62.2%). Conclusion This study highlights the need for innovative strategies for adolescents and parents to adopt and promote overall subjective wellbeing, especially during public health crises such as the COVID-19 pandemic.